THE MODEL OF POLITECHNIC MACHINING WORKSHOP MANAGEMENT WITH OCCUPATIONAL HEALTH AND SAFETY CHARACTER - Kuswanto, Bambang; Sastroatmodjo, Sudijono; Masruki, Masruki; Soesanto, Soesanto (The Journal of Educational Development, 2017)
As a practice, the Polytechnic machining workshop should also be a safe workplace for students. The lack of the manager’s attention in setting the safe way of working and the use of personal protective equipment for the students’ work show the substandard implementation of the occupational health and safety. This study aims to find out a factual management model, analyze the shortcomings, and design a hypothetical model for the Polytechnic machining workshop management characterized by health and safety. Students, lecturers, laboratory assistants, and technicians are directly related to the activities of the Polytechnic machining workshop as data sources. This study implemented research and development methodology, with data collection techniques that include observational studies, interviews, and questionnaires. Using indicators for safe machining workshop management, the result of each indicator shows merely 20% of the expectation. It was concluded that the factual management model to provide a safe workplace for students is still bad. The disadvantage of this management model is the lack of in-depth preparation for implementing occupational health and safety regulations. Therefore, the model still requires a development to become a model of machining workshop management with health and safety character. The success of the implementation of this management model requires leadership support and active participation of all those involved in the students’ practice activities in the Polytechnic machining workshop.